RELIGION THAT LEADS TO WAR RELIGION THAT LEADS TO PEACE: The Need to Adopt a Better Method of Teaching Religion if Peace is to Replace War - Fernando, Antony (Journal of Dharma, 2002)
As a general rule, all human beings by the very fact of their birth inherit a language they call their mother tongue and a religion they treat as their mother-religion. Language and religion are two distinct realities, but they have many aspects in common. An individual's first language and first religion are always those of the parents. They are learnt from early childhood almost from the time of breast-feeding. Parents are the first teachers of both